Regional and Gender Disparities in Abstracts Presented at the International Transplant Congresses - Ethier, Isabelle; Gaudio, Kathleen; Nijjar, Diya; Ramdane, Sabrina; Kim, Seokhwan Tommy; Ma, Maggie Kam-Man; Loban, Katya; Wong-Mersereau, Chloe; Cantarovich, Marcelo; Sandal, Shaifali (Transplantation, 2025)
Women and authors from low- and middle-income countries are notably underrepresented in academia. The intersection of these 2 factors is poorly quantified. We aimed to characterize gender disparities by region through analyzing abstracts presented at the Transplantation Society's congresses. Abstracts published in the supplements of the Transplantation journal were included (2016-2022). We used Genderize.io, a predictive algorithm, to classify the first and last authors' gender. Gender disparity was compared by the income level of the author's country of affiliation and the gender inequality index (GII), a composite metric with high scores representing higher levels of gender inequality. Of the 5005 abstracts analyzed (2259 oral presentations and 2746 posters), the majority emerged from high-income settings (low/lower middle: 7%, upper middle: 22%, and high: 71%). Excluding those for whom gender could not be reliably determined, only 39% of the first authors and 24% of the last authors were women. For 61% of the abstracts, the gender of the first and last authors was concordant, and women's last authorship was associated with a higher likelihood of women's first authorship (adjusted odds ratio: 1.88; 95% confidence interval: 1.62-2.14). Although gender disparity was observed across all income levels and GII scores, the proportion of women first authors declined significantly with lower national wealth (low: 19%, lower-middle: 23%, upper-middle: 42%, and high: 40%, P  < 0.001) and higher GII scores ( P  < 0.001). Our findings suggest that lack of resources and systemic gender inequities likely limit the progress and career development of women and researchers from low- and middle-income countries in transplantation globally. A deeper understanding of factors contributing to these disparities is needed.